Low-intensity land use fosters species richness of threatened butterflies and grasshoppers in mires and grasslands - Florian Fumy; Thomas Fartmann (Global Ecology and Conservation, 2023)
Insects are by far the most species-rich branch of the tree of life and fundamental parts of extensive networks of biotic interactions. However, insect populations are declining dramatically and many species are facing extinction in the course of global change. In this study, we investigated species richness of threatened butterflies and grasshoppers in mire and grassland ecosystems in a low-mountain range in SW Germany: the southern Black Forest. Altogether, 84 randomly selected plots (100 m × 100 m) were surveyed. Across a hydrological gradient, each plot belonged to one of the five following habitat types: peat bog, fen, mesic grassland, semi-dry grassland and dry grassland. Our study revealed strong differences in environmental conditions and in assemblage composition of threatened butterfly and grasshopper species in mire and grassland habitats. Species richness and the number of indicator species of both groups peaked in fens and dry grasslands, and to a lesser extent in semi-dry grasslands. All three habitat types were characterized by low to intermediate levels of land use. In line with this, land-use intensity was the key driver of habitat heterogeneity and, hence, of species richness of threatened butterflies and grasshoppers. We recommend a conservation policy that secures the maintenance or re-establishment of low-intensity land use. In particular, we suggest continuous large-scale, low-intensity cattle grazing from spring to autumn, which has been shown to best promote high habitat heterogeneity.